Fast tracking intensive care units and operation rooms during the COVID-19 pandemic in resource limited settings - Richa Aggarwal; Ridhima Bhatia; Kapil Dev Soni; Anjan Trikha (Wolters Kluwer Medknow Publications, 2020)
The ongoing pandemic of COVID-19 has affected more than 43 million people all over the world with about 280000 deaths worldwide at the time of writing this article The outcome of this pandemic is impossible to predict at the present time as the numbers of both, infected patients and those dying of the disease are increasing on a daily basis. China, Italy, France, Spain, Germany, United Kingdom, and USA are the worst affected countries. All these countries have robust health care systems but despite this there has been a huge shortage of health care facilities especially intensive care beds in these countries. A country like India has different challenges as far as medical care during this pandemic is concerned. The need of the hour is to improve the health care system as a whole. In the present pandemic this involves setting up of patients screening facilities for the disease, enhancing the number of hospital beds, setting up of dedicated high dependency units, intensive care units and operation theatres for COVID positive patients. The present article describes in brief the way this can be done in a short time.